2019
DOI: 10.1111/crj.13134
|View full text |Cite
|
Sign up to set email alerts
|

Association between venous thromboembolism and acute pancreatitis: An analysis from the nationwide inpatient sample

Abstract: Background and Aims Acute inflammation of the pancreas may trigger a systemic inflammatory response and initiate coagulation. Few studies have been conducted on the association between venous thromboembolism (VTE) and acute pancreatitis (AP). We investigated the incidence and risk of VTE in patients with AP. Methods We conducted a retrospective cohort analysis for the nationwide AP cohort. We identified 91 786 patients with AP and 183 557 controls who were frequency‐matched according to sex, age (5‐y interval)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The occurrence and development of thrombotic diseases are not only related to abnormal blood coagulation and fibrinolysis processes but also to intravascular inflammation. Chung et al (32) showed that thrombosis is also an inflammatory reaction process because there is a close relationship between inflammatory reaction and thrombosis. The massive release of inflammatory mediators and the damage to the vascular endothelium during infection leads to platelet adhesion and aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence and development of thrombotic diseases are not only related to abnormal blood coagulation and fibrinolysis processes but also to intravascular inflammation. Chung et al (32) showed that thrombosis is also an inflammatory reaction process because there is a close relationship between inflammatory reaction and thrombosis. The massive release of inflammatory mediators and the damage to the vascular endothelium during infection leads to platelet adhesion and aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Sahni et al (35) also reported that the serum level of Ang-2 is positively correlated with inflammatory mediators such as TNF-α and interleukin 6, and these two inflammatory factors have been proved to be risk factors for DVT in many studies. As a pro-inflammatory factor, Ang-2 plays an important role in the physiological activities of promoting inflammation and vascular leakage (32). D-dimer is not only the smallest fibrin degradation product but also a specific degradation product of the fibrous matrix of venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that this cohort is at a higher risk for VTE than the control patients, irrespective of age, sex, or comorbidities. The patients showed a 1.86-fold higher adjusted hazard ratio (aHR) of DVT and a 1.92-fold higher aHR of pulmonary embolism than did the controls [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to pancreatitis, the systemic acute inflammatory process increases pro-inflammatory markers such as TNF-alpha, IL-1, IL-6, IL-10, which then trigger the activation of the coagulation cascade, prevent fibrinolysis, and prevent regular anticoagulation pathways from functioning. [5] Endothelial vasculature is disrupted through the activation of inflammatory markers, leading to the weakening of vessel walls. This, in turn, leads to impediment of blood flow and stasis which allow for ensuing thrombus formation.…”
Section: Discussionmentioning
confidence: 99%